A reversibly transformable chromatic system of the (octaethylporphyrin)-(dihexylbithiophene)-(Lewis base) triads. An evaluation of stereo-electronically controlled effects of dihexylbithiophene and Lewis base on its sensitivity and stability to trifluoroacetic acid. Issue 8 (25th February 2015) - Kempe, Hideto; Yoshino, Junro; Hayashi, Naoto; Higuchi, Hiroyuki
Abstract: The extended π-electronic conjugation system of the (octaethylporphyrin)-(dihexylbithiophene)-(Lewis base) triads [OEP-DHBTh-LB] exhibits the proton-mediated reversible changes in both 1 H NMR and UV–vis spectra via two-step processes, reflecting the structural features of DHBTh and LB constituents. The spectral changes of OEP-DHBTh-LB with trifluoroacetic acid (TFA) were quantitatively examined by means of 1 H NMR spectral measurement and comparatively analyzed in terms of stereo-electronically controlled effects of DHBTh and LB constituents on its reversibly transformable chromatic system. Successively, based on the minimum amount of TFA necessary for completion of spectral changes at respective steps, the sensitivity and stability of OEP-DHBTh-LB to TFA were evaluated, from the viewpoint of the interactive behavior of the lone pair electrons on N atom in LB with the extended OEP constituent. The present study provides a useful guideline of the molecular design for further sophisticated OEP-based chromatic system with proton-sensing functionality. Graphical abstract: